1985
DOI: 10.1002/chin.198524362
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: NITRARIA KOMAROVII ALKALOIDS. VIII. SYNTHESIS AND PHARMACOLOGICAL PROPERTIES OF NITRAMARIN ALKALOID

Abstract: Nitramarin (IV), ein neues Alkaloid aus Nitraria komarovii Iljin et Lava (Gruppe Zygophyllaceae), wird durch Kondensation von Tryptamin (I) mit Chinaldinaldehyd (II) (aus Chinaldinund Selendioxid in 65 % Ausbeute) und anschließende Dehydrierung hergestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Nitramarine ( 3 ) (Figure ) is a α-quinolinyl-β-carboline alkaloid, which was isolated from Nitraria komarovii plant by Tulyaganov et al in 1984 . It exhibits sleeping time pronging effect, hypotensive and spasmolytic activities .…”
Section: Resultsmentioning
confidence: 99%
“…Nitramarine ( 3 ) (Figure ) is a α-quinolinyl-β-carboline alkaloid, which was isolated from Nitraria komarovii plant by Tulyaganov et al in 1984 . It exhibits sleeping time pronging effect, hypotensive and spasmolytic activities .…”
Section: Resultsmentioning
confidence: 99%
“…2.6.2 Nitramarine Nitramarine (see 13) an alkaloid of Nitraria komorovii possesses hypotensive and spasmolytic activities (TULYAGANOV et al 1984). …”
Section: Ch3mentioning
confidence: 99%
“…Of the hundreds of β-carboline-containing natural products, only a few contain different aryl or heteroaryl functionality at the 1-position, including eudistomins A, M, and U, nitraridine and nitramarine, and chaetogline F (Figure ). However, it is unclear what role these groups play in their observed biological activity. We have shown that eudistomin U has weak unspecific binding to DNA, but no detailed studies of this substitution pattern and its effect on bioactivity have been performed .…”
Section: Introductionmentioning
confidence: 99%